2023
DOI: 10.3389/fgene.2022.1068462
|View full text |Cite
|
Sign up to set email alerts
|

Cell death-related biomarker SLC2A1 has a significant role in prognosis prediction and immunotherapy efficacy evaluation in pan-cancer

Abstract: Introduction: SLC2A1, a member of the SLC transporter family, is involved in a variety of cell death modalities and has been found to be associated with the prognosis and immune microenvironment of a variety of tumors. However, there is a lack of systematic and comprehensive studies on the role of SLC2A1 in pan-cancer.Methods: The mRNA, promoter methylation, and protein expression levels of SLC2A1 in pan-cancer were comprehensively evaluated using GEPIA2.0, TIMER2.0, and UALCAN databases. UCSCXenaShiny based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Using the established expression markers, such as for endothelial cells ( KLF2 )(Sangwung, Zhou et al . 2017), M2 macrophages ( SLC2A1 )(Wang, Wang et al . 2023), TNBC cancer cells ( TRPS1 )(Ai, Yao et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the established expression markers, such as for endothelial cells ( KLF2 )(Sangwung, Zhou et al . 2017), M2 macrophages ( SLC2A1 )(Wang, Wang et al . 2023), TNBC cancer cells ( TRPS1 )(Ai, Yao et al .…”
Section: Resultsmentioning
confidence: 99%
“…Cells were clustered based on specific cell markers. Using the established expression markers, such as for endothelial cells ( KLF2 )( 31 ), M2 macrophages ( SLC2A1 )( 32 ), TNBC cancer cells ( TRPS1 )( 33 ), proliferating cells ( TOP2A) ( 34 ), myeloid cells ( FTH1) ( 35 ), progenitor cells ( NES )( 36 ), adipocytes ( CLEC11A )( 37 ), mesenchymal cells ( S100A4 )( 38 ), angiogenic cells ( RPL35A )( 39 ), breast cancer stem cells (FXYD3 )( 40 ), dendritic cells ( CD68 ) ( 41 ), cancer-associated fibroblast ( COL1A2 )( 42 ), epithelial cells ( EPCAM )( 43 ), cycling cells ( CDK4 )( 44 ), and B-cells ( CD83 ) ( 45 ), we found that CRD altered different cell populations in the TME (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have investigated its role as a prognostic and immunotherapeutic marker in lung adenocarcinoma [25], where it was found to be aberrantly expressed in numerous cancers. Furthermore, SLC2A1 has shown prognostic significance and plays a role as an immune marker in various other cancers [26][27][28]. In the study of non-tumor diseases, evidence suggests that high expression of SLC2A1 is associated with type 2 diabetes and its complications [29], as well as chronic inflammation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GO analysis also showed that Endo cluster3 was mainly enriched in the pathways of cell proliferation, migration, positive regulation of cell activation, and epithelial-to-mesenchymal transition (Fig 5D). SLC2A1, a member of the SLC transporter protein family, is primarily involved in encoding glucose transporter proteins at the cell membrane and cell surface [27]. Importantly, SLC2A1 has been reported to promote cancer development by regulating cell proliferation [28].…”
Section: Heterogeneity Of Epithelial Cell Subpopulations In Ec In Res...mentioning
confidence: 99%
“…SLC2A1 is a member of the SLC transporter protein family and is able to participate in a variety of cell death modalities. Wang and his colleagues comprehensively summarized the prognostic role of SLC2A1 in pan-cancer and found that SLC2A1 is able to be overexpressed in a wide range of tumors and is associated with a poor prognosis in patients [27]. Moreover, SLC2A1 has been shown to be a key gene in tumor glucose metabolism, which promotes glycolysis in cancer cells and thus affects the growth and metastasis of cancer cells [45,46].…”
Section: Plos Onementioning
confidence: 99%